Pengaruh Digital Marketing dan Literasi Ekonomi Syariah terhadap Pendapatan UMKM di Kecamatan Wonosari Kabupaten Bondowoso: The Influence of Digital Marketing and Sharia Economic Literacy on MSME Income in Wonosari District, Bondowoso Regency - Rohmatillah, Wildania; Viphindrartin, Sebastiana; Suparman, Suparman (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2025)
MSMEs play an important role in the Indonesian economy, including in Wonosari District. With the number of business actors reaching 1,260, this sector has great potential to grow. However, challenges such as low adoption of technology and sharia economic literacy are the main obstacles. Many business actors still rely on traditional marketing methods and are hesitant to switch to digital marketing. Transformation through the implementation of digital marketing supported by sharia economic literacy is expected to increase MSME income. This study aims to analyze the influence of digital marketing and sharia economic literacy on MSME income in Wonosari District. This study uses a quantitative method, with primary data obtained through questionnaires and secondary data from trusted sources. Data analysis was carried out using multiple linear regression. The results of the study show that digital marketing and sharia economic literacy have a positive and significant influence on MSME income in Wonosari District, Bondowoso Regency.